Manajemen Peningkatan Mutu Pendidikan di Pondok Pesantren Al-Husna Samarinda Seberang - A’an Yusuf Khunaifi; Nanda Fajrul Hanif (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Overall the scope of IPS learning is the integration of individuals into their social environment. While the learning model is a learning strategy with a structured procedure or pattern that is used as a guide to achieving goals. Therefore, this study aims to describe the conceptual learning model that links real life examples in the integrative thematic approach to social studies subjects. The conceptual model is a learning model that applies in integrating the daily lives of students and then is used as a value material in learning. This study uses the library research method, by examining some of the literature on conceptual learning models that are applied into Social Sciences (IPS) subjects. So it can be said, the conceptual model is an innovation in the world of education, which is a form of development of the old model.